2016
DOI: 10.1080/09589236.2016.1223619
|View full text |Cite
|
Sign up to set email alerts
|

Enacting motherhood: time and social change in Chile

Abstract: Motherhood is changing. An increasing number of women are deciding to remain childless, having fewer children, postponing their transition to motherhood, and simultaneously pursuing careers. These changes are deeply embedded in a reconfiguration of the times of motherhood. Although the intersection of motherhood and time has been widely acknowledged by gender and feminist studies, less attention has been paid to how in the making of motherhood women reproduce, negotiate and subvert time mandates and norms. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
1
5
0
2
Order By: Relevance
“…Consequently, Chile would by characterized today by a late fertility structure where women aged 30-34 years have the highest childbearing rates in the country (Instituto Nacional de Estadísticas, 2014b). This is consistent with a qualitative study conducted by Yopo (2016), which demonstrates that women are postponing the transition to motherhood because of emerging cultural norms that suggest that they should have children only after achieving, for example, a good financial status to have an adequate household and the resources to educate and nurture their children. Arriagada (2004) has suggested that in Latin American countries undergoing a second demographic transition, a growing number of couples would decide to remain childless.…”
Section: Interpreting Cultural and Social Change In Chilesupporting
confidence: 88%
“…Consequently, Chile would by characterized today by a late fertility structure where women aged 30-34 years have the highest childbearing rates in the country (Instituto Nacional de Estadísticas, 2014b). This is consistent with a qualitative study conducted by Yopo (2016), which demonstrates that women are postponing the transition to motherhood because of emerging cultural norms that suggest that they should have children only after achieving, for example, a good financial status to have an adequate household and the resources to educate and nurture their children. Arriagada (2004) has suggested that in Latin American countries undergoing a second demographic transition, a growing number of couples would decide to remain childless.…”
Section: Interpreting Cultural and Social Change In Chilesupporting
confidence: 88%
“…Data from Instituto Nacional de Estadísticas (2018) demonstrate that the fertility rate in Chile has declined from 5.4 in 1962 to 1.69 in 2016, almost 70 per cent in the course of 50 years. Together with the above, studies conducted in the last decade also reveal a sustained increase of late fertility intentions and practices among Chilean women (Cerda, 2010; Fuentes et al., 2010; Yopo Díaz, 2018a, 2020). Women's average age at first childbearing has increased from 22.47 years in 1972 to 25.04 years in 2016 (Instituto Nacional de Estadísticas, 2019) and women from 25 to 34 years old have the highest contribution to the fertility of the country (Instituto Nacional de Estadísticas, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…The motherhood discourse within the Latin American context is understood at the core of femininity ( Alvarez Minte et al, 2021;Barrancos, 2007) and deeply ingrained in societal and cultural mandates towards women's role in childcare (O'Connor, 2014;Ramm, 2020;Yopo D ıaz, 2018). While the exact imaginations and expectations towards motherhood differ across regions, social classes and ethnicities, the importance of mothers within society and the role of motherhood in women's lives is shared within the Latin American context.…”
Section: Literature Reviewmentioning
confidence: 99%